Institutional and technological innovation for the bamboo sector as an instrument for development and climate change resilience in Ethiopia. Issue 7 (10th November 2021) - Endalamaw, Tefera Belay; Darr, Dietrich
Abstract : Given a huge resource base, numerous product and service functions, bamboo can top many of the species recommended for integrated rural development in the context of climate change. Despite this potential, there is gap in knowledge and innovation to make optimum use of this resource. This study provides insights into the need for and processes of institutional and technological innovation to materialize bamboo's potential. The study is based on the theory of systems of innovation and empirical data collected from bamboo farmers, enterprises and 26 experts. The results demonstrate that traditional knowledge and technical skills in rural areas are key sources of knowledge for product innovation and climate change adaptation. The study reveals that enterprises have a primary role both in the generation of innovation and the production of value-added products. Institutional actors (GOs and NGOs) play an intermediary role in promoting bamboo sector innovation through training provision, policy development and stimulating social learning among actors. The study reveals that further effort is needed to upgrade the capacity of farmers and firms to produce globally competitive products. Therefore, development should be geared towards establishing and nurturing a bamboo sector innovation system which facilitates entry into the global value chain.